DESIGN OF A 12-STORY HIGH-RISE RESIDENTIAL BUILDING IN SAN FRANCISCO, CALIFORNIA, USA - Kadyrov, Aliyar; Sagidolla, Aldiyar; Gumarov, Ramir; Sagyndykova, Zhaniya; Baktiyarkyzy, Ayaulym; Yelubayev, Arsen; Yergeldinov, Bek (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This paper presents the design and construction proposal for a 12-story residential building located at 1335 6th St, San Francisco, California, USA. The location offers a blend of residential, commercial, and mixed-use developments. Urbanization and a shortage in housing within the city have accelerated the need for innovative residential construction solutions, necessitating a comprehensive approach that incorporates architectural, structural, material, and geotechnical considerations. The building’s architectural design complies with the standards outlined in the International Building Code (IBC). The structural design follows the guidelines of the American Concrete Institute (ACI) and the American Society of Civil Engineers (ASCE), with SAP 2000 software employed to perform structural analyses and simulate the building's response to gravity and lateral forces. Reinforced concrete has been chosen as the primary construction material due to its availability, versatility, and cost-efficiency. A comparative analysis of foundation options, supported by geotechnical studies, identified a pile foundation as the most suitable solution for supporting the superstructure. The stormwater management design includes sustainable drainage through the use of permeable surfaces and green infrastructure to reduce runoff and risks of flooding. Full construction management strategies include estimating costs, scheduling, risk assessment, and follow-through with LEED standard to provide a safe, environmentally responsible execution process. This development will realise an integrated approach to urban residential construction through innovative design, sustainability, following international and local building codes.
Keywords: Design; Construction; Residential Building; San Francisco; California; USA; Architectural design; structural design; geotechnical analysis; stormwater water design; construction management; type of access: open access